Using Data Mining Technology to Improve the Reliability of Accounting Information Cloud Data - Li, Bo (Informatica, 2025)
This study uses data mining technology to improve the reliability of accounting information cloud data, and realizes accurate classification and anomaly detection of data through systematic data cleaning and processioning, optimization and application of support vector machine model. After analyzing data integration and normalization processing, model construction and optimization strategy, performance evaluation and optimization, the optimized SVM model has achieved improvement in data processing efficiency, data accuracy and consistency. Emphasize the importance of data security and privacy protection to ensure the security of data during transmission and storage. This study provides reliable data support for enterprise financial management and decision-making, and promotes the development of accounting normalization.